314 Hyperoxia Changes the Balance of the Thioredoxin/Peroxiredoxin System in the Neonatal Rat Brain. (October 2012) - Strasser, K; Bendix, I; Weichelt, U; Endesfelder, S; Haefen, C von; Heumann, R; Ehrkamp, A; Buehrer, C; Felderhoff-Mueser, U; Sifringer, M
Abstract : Background and Aim: As demonstrated previously, oxygen contributes to the pathogenesis of neonatal brain damage and leading to neurocognitive impairment of prematurely born infants in later life. Reactive oxygen species (ROS) and intrinsic antioxidant defense systems play an important role in both physiological cell signaling processes and many pathological conditions, including neurodegenerative disorders and oxygen-toxicity. Beside the glutathione-system several other redox-modulating proteins are known to be involved in redox-homeostases. The aim of this study was to evaluate potential alterations within the thioredoxin/peroxiredoxin system after exposures to nonphysiologic high oxygen levels in the developing rat brain. Methods: Six-days old Wistar rats were exposed to 80% oxygen for 6, 12, 24 or 48 hours and littermates kept in room air served as controls (n=6–8). Brains (excluding cerebellum) were evaluated after perfusion with PBS and dissection of both hemispheres for RNA and protein analyses. Results: We demonstrate that elevated oxygen concentrations change the balance of the ROS-dependent thioredoxin/peroxiredoxin system. Oxygen-toxicity significantly induced upregulation of peroxiredoxins in infant rat brain. In parallel, hyperoxia reduced the level of DJ-1, a hydroperoxide-responsive protein. Discussion: These findings are highly relevant from a clinical aspect because oxygen administration to neonates is often inevitable, and we recommend that every effort should be made in neonatal medicine to limit exposure of these immature babies to high oxygen concentrations. These results may also contribute to receive optimal therapeutical approaches to ameliorate oxygen toxicity.